Hubungan Pengetahuan Pola Asuh Dan Pola Makan Pada Balita - Marlina Rajagukguk (Anthropos: Jurnal Antropologi Sosial dan Budaya (Journal of Social and Cultural Anthropology), 2022)
The impact of food and the use of nutrients consumed by a person that affects the state of a person's body is called nutritional status. Nutritional status is divided into several indicators. In 2017, UNICEF stated that there were 51 million (7.5%) under-fives experiencing wasting, 151 million (22%) under-fives experiencing stunting and 92 million (13.5%) under-fives in the world. The research was conducted using the literature study method or literature review that focuses on the results of writing related to the relationship eating parenting with nutritional status in toddlers through searching accredited journal sites such as Google Schoolar, Google, and Pubmed, in the 2017-2021 period. Based on the research that has been done, there is a relationship between eating parenting and nutritional status in toddlers.